Extra-Amniotic Infusion of Corticosteroids versus Normal Saline for Cervical Ripening and Shortening of 1st Stage of Labour in Mid Trimester Termination of Pregnancy Sadaf Sahar, Tabassum Firdous, Asifa Alia, Nusrat Manzoor - Sadaf Sahar, Tabassum Firdous, Asifa Alia, Nusrat Manzoor, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Pregnancy termination is still a big challenge for Obstetrician specifically in case when the Cervix is not ripped. Recently it was shown that the extra amniotic infusion of corticosteroids is superior in terms of mean duration of first stage of labour and frequency of cervical Ripening to the conventional practice of extra-amniotic infusion of normal saline. However, the limited data and lack of local research material necessitated this study. Objective: The objective of this study was to compare outcome of extra-amniotic infusion of corticosteroids versus normal saline for cervical ripening and mean duration of 1st stage of labour in mid trimester termination of pregnancy. Material & Methods: It was a randomized controlled trial. Research was conducted at Department of Obstetrics & Gynecology Rai Medical College Teaching Hospital, Sargodha from 10/01/2022 to 09/06/2022. This study involved 100 pregnant women aged between 18-40 years undergoing termination of pregnancy between 14-28 weeks of gestation (as per dating scan). These patients were randomly allocated into two groups. Patients in Group-A were given extra-amniotic infusion of corticosteroids while those in Group-B received extra-amniotic infusion of normal saline. Outcome variables were mean duration of first stage of labor and frequency of cervical ripening which was noted and compared between the groups. A written informed consent was taken from each patient Results: The mean duration of first stage of labor was significantly shorter in women receiving extra-amniotic infusion of steroids as compared to normal saline (178.94±34.19 vs. 237.20±24.84 minutes; p-value<0.001). The frequency of cervical ripening was significantly higher in women receiving extra-amniotic infusion of steroids as compared to normal saline (96.0% vs. 72.0%; p-value=0.001). Conclusion: Extra-amniotic infusion of corticosteroids was found superior to conventional practice of normal saline in terms of significantly higher frequency of cervical ripening and significantly shorter mean duration of 1st stage of labor which is desirable in women undergoing mid-trimester termination of pregnancy and advocates preferred use of extra-amniotic infusion of corticosteroids in future obstetric practice Keywords: Mid-Trimester Abortion, Cervical Ripening, Steroids, Extra-amniotic Infusion